A Cost Effective Process for Large Area Photonic Array Applied in Light Emitting Diodes for Light Extraction Enhancement. (14th August 2019) - Zhu, Jingyuan; Sun, Zhijiang; Chen, Yifang; Lu, Bing-Rui
Abstract : The rise of the electricity-to-light conversion rate in light emitting diodes (LEDs) for energy saving has been constantly demanded. One of the keys to elevate the efficiency is to enhance the light extraction by using photonic structure covering on the window above the LEDs. This involves both designing and replicating the nanophotonic structures on transparent wafers. The techniques for micro-nano structuring should be high efficient and low cost for large volume production. This paper reports our recent progress in developing an industrialization prospective process for a planar photonic crystal in silicone to enhance the light extraction from LEDs in chip scale package (CSP) by template casting and film transfer. Characterizations of light extraction through the crystals and illumination from the LEDs demonstrate the significant improvement of the LED performance.